Photocatalytic setup for in situ and operando ambient-pressure X-ray photoelectron spectroscopy at MAX IV Laboratory - Klyushin, Alexander; Ghosalya, Manoj; Kokkonen, Esko; Eads, Calley; Jones, Rosemary; Nalajala, Naresh; Gopinath, Chinnakonda S.; Urpelainen, Samuli (Journal of Synchrotron Radiation, 2023)
The Ambient-Pressure X-ray Photoelectron Spectroscopy (APXPS) endstation at the SPECIES beamline at MAX IV Laboratory has been improved. The latest upgrades help in performing photo-assisted experiments under operando conditions in the mbar pressure range using gas and vapour mixtures whilst also reducing beam damage to the sample caused by X-ray irradiation. This article reports on endstation upgrades for APXPS and examples of scientific cases of in situ photocatalysis, photoreduction and photo-assisted atomic layer deposition (photo-ALD).
Keywords: APXPS; photo-ALD; Photocatalysis; solar simulator